The archaeology of Australia's deserts - Smith, Mike 1955- (Cambridge University Press, 2013)
This is the first book-length study of the archaeology of Australia's deserts, one of the world's major habitats and the largest block of drylands in the southern hemisphere. Over the last few decades, a wealth of new environmental and archaeological data about this fascinating region has become available. Drawing on a wide range of sources, The Archaeology of Australia's Deserts explores the late Pleistocene settlement of Australia's deserts, the formation of distinctive desert societies, and the origins and development of the hunter-gatherer societies documented in the classic nineteenth-century ethnographies of Spencer and Gillen. Written by one of Australia's leading desert archaeologists, the book interweaves a lively history of research with archaeological data in a masterly survey of the field and a profoundly interdisciplinary study that forces archaeology into conversations with history and anthropology, economy and ecology, and geography and Earth sciences
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Archäologie; Deserts / Australia; Environmental archaeology / Australia; Archaeology / Australia; Human ecology / Australia; Geschichte; Wüste; Siedlungsarchäologie; Humanökologie; Australien